Aldehyde-specific responses of olfactory sensory neurons in the praying mantis - Kota Ezaki (Nature Portfolio, 2021)
Abstract Although praying mantises rely mainly on vision for predatory behaviours, olfaction also plays a critical role in feeding and mating behaviours. However, the receptive processes underlying olfactory signals remain unclear. Here, we identified olfactory sensory neurons (OSNs) that are highly tuned to detect aldehydes in the mantis Tenodera aridifolia. In extracellular recordings from OSNs in basiconic sensilla on the antennae, we observed three different spike shapes, indicating that at least three OSNs are housed in a single basiconic sensillum. Unexpectedly, one of the three OSNs exhibited strong excitatory responses to a set of aldehydes. Based on the similarities of the response spectra to 15 different aldehydes, the aldehyde-specific OSNs were classified into three classes: B, S, and M. Class B broadly responded to most aldehydes used as stimulants; class S responded to short-chain aldehydes (C3–C7); and class M responded to middle-length chain aldehydes (C6–C9). Thus, aldehyde molecules can be finely discriminated based on the activity patterns of a population of OSNs. Because many insects emit aldehydes for pheromonal communication, mantises might use aldehydes as olfactory cues for locating prey habitat.